Investigating the biological impact of pharmaceutical pollutants exposure towards Malaysian polychaetes, marphysa moribidii and diopatra claparedii using nuclear magnetic resonance-based metabolomics / Dr. Hisyam Abdul Hamid ... [et al.] - Abdul Hamid, Hisyam; Husain, Noreen; Ali Shah, Syed Adnan; Wan Ismail, Wan Iryani; Idris, Izwandy (Faculty of Pharmacy, 2023)
There were numerous studies conducted globally and pointed out potential role of polychaete or locally known as "umpun-umpun" in the field of nature conservation, economy and even medical use. The polychaetes construct, ingest particles and irrigating activity is vital for marine ecosystems. The presence of polychaetes and different species in an integrated multi trophic aquaculture can improve efficacy, reduce waste and provide ecosystem services potentially lead to significant economic, social, and ecological benefits. In fact, the polychaetes are commonly used as fish baits. In Malaysia, the selling price of polychaetes can be up to RM1 each and probably higher depending on the size.